Molecular scylla and charybdis: Maneuvering between pH sensitivity and excited-state localization in ruthenium Bi(benz)imidazole complexes - Mengele, Alexander K.; Müller, Carolin; Nauroozi, Djawed; Kupfer, Stephan; Dietzek, Benjamin; Rau, Sven (Inorganic Chemistry, 2020)
Bi(benz)imidazoles (b(b)im) acting as N,N-chelates in ruthenium complexes represent a unique class of ligands. They do not harbor metal-to-ligand charge-transfer (MLCT) excited states in ruthenium polypyridyl complexes upon visible-light excitation provided that no substitution is introduced at the N atoms. Hence, they can be used to steer light-driven electron-transfer pathways in a desired direction. Nonetheless, the free N atoms are susceptible to protonation and, hence, introduce highly pH-dependent properties into the complexes. Previous results for ruthenium complexes containing R2bbim ligands with alkylic or arylic N,N′-substitution indicated that, although pH insensitivity was accomplished, unexpected losses of spectator ligand features incurred simultaneously. Here, we report the synthesis and photophysical characterization of a series of differently N,N′-alkylated b(b)im ligands along with their corresponding [(tbbpy)2Ru(R2b(b)im)](PF6)2 complexes (tbbpy = 4,4′-tert-butyl-2,2′-bipyridine). The data reveal that elongation of a rigid ethylene bridge by just one methylene group drastically increases the emission quantum yield, emission lifetime, and photostability of the resultant complexes. Quantum-chemical calculations support these findings and allow us to rationalize the observed effects based on the energetic positions of the respective excited states. We suggest that N,N′-propylene-protected 1H,1′H-2,2′-biimidazole (prbim) is a suitable spectator ligand because it stabilizes sufficiently long-lived MLCT excited states exclusively localized at auxiliary bipyridine ligands. This ligand represents, therefore, a vital building block for next-generation photochemical molecular devices in artificial photosynthesis.
CRIS-Team Scopus Importer:2023-11-13